Serotonin, Endorphin Concentrations and Some Hematological Parameters in Male Narghile Smokers - Salim Jasim Khalaf; Mahdi Salh Hamad; Nahla Kamal Asaad (Tikrit Journal of Pure Science)
This study was carried out to evaluate the relationship between narghile smoking and serum concentration of serotonin and endorphin and some blood hematological indices in males. Group of smokers composed of 50 voluntary, and control group composed of 36 healthy voluntary. This study was conducted on adults man that ages between (18-25 years). The markers measured in this study were serum serotonin and endorphin and hematological indices (platelets, hematocrit, hemoglobin, and white blood cells).